Natural VR modeling: a viable alternative to freehand sketching for preliminary design? - Harlan, Jakob; Götz, Stefan; Wartzack, Sandro (Design Science, 2025)
The ideating phase of product design is critical, as decisions made here influence the rest of the product’s lifecycle. Usually, early preliminary designs in engineering are created with pen and paper, which are incompatible with the subsequent digital design process. In an effort to find a modeling tool for early designs that provides the creative flexibility of freehand sketching but also the further processability of digital models, this research investigates natural modeling in virtual reality (VR). To do so, a VR modeling method allowing the intuitive creation of preliminary designs as simplified computer-aided design (CAD) models is presented. The main contribution is the evaluation of this natural VR modeling method against freehand sketching in an extensive user stud
Keywords: Virtual Reality (VR); Computer-Aided Design (CAD); Preliminary Design; Engineering Design; Natural User Interfaces